Carbon coated NASICON type Li3V2-xMx(PO4)3 (M=Mn, Fe and Al) materials with enhanced cyclability for Li-Ion batteries - Son, J. N. (2013)
We report the synthesis and optimization of metal (Mn, Fe and Al) doped NASICON type Li3V2(PO4)3 by solid-state reaction method. Among the metal doping, 0.02 mol concentration of Al is found better performing electrode while approaching the removal of three moles of lithium between 3-4.8 V vs. Li. Adipic acid with various concentrations is used to generate in-situ carbon layer over the 0.02 mol Al doped Li3V2(PO4)3 particulates (Li3V1.98Al0.02(PO4)3). Presence of carbon on the surface of particulates is confirmed by TEM and Raman analysis. Half-cell Li/C-Li3V1.98Al0.02(PO4)3 (0.15 mol of adipic acid) exhibited the highest reversible capacity of ∼182 mAh g−1 (2.77 moles of lithium) at a current density of 0.1 mA cm−2 compared to rest of the adipic acid concentrations. Further, the cell retained 83% of capacity after 50 galvanostatic charge-discharge cycles at ambient conditions. Li-insertion/extraction mechanism and improvement in electronic conductivity profiles are validated through cyclic voltammetry and electrochemical impedance spectroscopy, respectively.